Subaltern Subjectivation of Dalit Women in Bangladeshi Fiction: A Study of Harishankar Jaladas’s Sons of the Sea - Nur E Jahan Tahin; Arnab, Nafis Jamal (International Journal of Language and Literary Studies, 2025)
In recent years, subaltern discussion in mainstream literature, humanities, and social sciences has extended the subaltern question into Dalit existence and literature. While Dalit subalternity is a pressing issue in scholarly discussions, there is a substantial inadequacy of critical attention given to Dalit women, especially in Bangladeshi fiction. However, Harishankar Jaladas’s rootedness in the Dalit community and a firm belief in the deconstruction and reconstruction of the asymmetric caste stratifications led the author to propagate an artistic gesture for the sublimation of the suppressed. Being a Dalit himself, Jaladas engages in various subaltern subjectivation, including the intersectional position of Dalit women. As Spivak says, this subjectivization is in opposition to the ‘objectivisation’ of the subaltern by non-subaltern writers. Therefore, this paper presents an investigation into the unexplored plight of Dalit women and their subsequent descent into subalternity using Jaladas’ novel Sons of the Sea as the primary source of analysis. Keeping Spivak’s arguments on female subalternity and its association with casteism at heart, it contextualizes Jaladas’ Dalit Jaladasis (a term Jaladas has employed as the feminine form of Jaladas/Jele/Fisherman) into the subaltern question. Moreover, it offers an unerring illustration of how their perpetual suffering breeds resistance and counter contexts transcending patriarchal and casteist frameworks. For an objective and extensive analysis, theoretical concepts from diverse yet relevant sources and fields of Dalit subalternity and feminism have been investigated and brought to bear in this paper.